Two teenagers, traumatic aortic disruption, and transoesophageal echocardiography. Issue 3 (September 1997) - Absalom, A.; Burns, A.; Wells, F.; Stone, D.
Abstract : A report of two teenagers is presented who were passengers of the same vehicle when it was involved in a serious road traffic accident. Their vehicle was hit on the side at high speed by a second vehicle. Both teenagers sustained multiple injuries. On arrival at a district general hospital they required resuscitation, exploratory laparotomies, and postoperative intensive care. Neither had radiographic evidence to suggest any mediastinal injury, but transoesophageal echocardiography demonstrated aortic disruption in both patients. They were transferred to a regional cardiothoracic centre where their lesions were successfully repaired and both have made a full recovery.